Pelatihan Dan Penyuluhan Pembuatan Lilin Aromaterapi Dari Limbah Tembakau Di Desa Gunungrejo Kedungpring Lamongan - Februyani, Nawafilla; Ifnu, Ifnu Wisma Dwi Prastya (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2025)
Background: Tobacco is an important agricultural commodity with various benefits, including for natural pesticides, cosmetics, and essential oils. One potential innovation from tobacco waste is the manufacture of aromatherapy candles, which have health benefits such as reducing stress and improving quality of life. This community service program aims to utilize tobacco waste through training and counseling on making aromatherapy candles for 25 PKK members of Gunungrejo Village, Kedungpring District, Lamongan Regency. Methods: The methods used include counseling, socialization of the benefits of aromatherapy candles, and candle-making practices. Results: The results of the program showed an increase in participant understanding from 47.9% to 98.2% based on the pretest and posttest. Conclusions: In addition to social benefits in the form of health awareness and community strengthening, this program also opens up economic opportunities with the potential for increased income through the development of aromatherapy candle businesses based on tobacco waste.